Spontaneous multilevel lumbar pediculolysis associated with spondylolysis: a rare case and review of the literature - Zan Chen; Yusheng Bao; Daxiong Feng; Yinxiao Peng; Fei Lei (BMC Musculoskeletal Disorders)
Abstract Background Pediculolysis is bone hypertrophy and pseudoarthrosis caused by pedicle fracture and has often been combined with contralateral spondylolysis in previous reports. Multilevel pediculolysis with spondylolysis is extremely rare, and we report a case who underwent surgery. Cases of multisegment pediculolysis were reviewed to inspire the diagnosis and treatment of similar pathological phenomena. Case presentation A 55-year-old man suffering from low back pain and sciatica was admitted to hospital after failing conservative treatment. The imaging studies revealed bilateral pediculolysis at L3 and L4 and right spondylolysis at L5. When L2-5 internal fixation and fusion surgery were performed, the symptoms improved immediately after surgery. At the 2-year postoperative follow-up, proximal junctional failure appeared and progressively worsened. Conclusions Multilevel pediculolysis often requires surgical intervention, and segment instability is an important consideration in the development of surgical fusion strategies. The etiology of pediculolysis is still complex and unknown, and the spondylolysis protocol can be used as a reference for treatment. Surgeons should be cautious in surgical planning to minimize the likelihood of postoperative instrumentation failure.